Forging orientalism in royall taylor’s the algerine captive - Walid MOKHTARI (Akofena, 2023)
Abstract: Travel writing was almost a precursor to what Said calls Orientalism. In the nineteenth century, Algeria displayed an overwhelming sovereignty over the Mediterranean that the countries of the West used to pay tributes to Algiers to get their trading ships to pass. The Algerine corsairs captivated ships, and captivity writings got popular displaying the difficult circumstances of the captives such as Royall Tyler’s The Algerine Captive (1797). The noveldocuments the journey of an American doctor named Updike Underhill through captivity in Algiers. It brought about an image of the kind of relationship the nascent United States had with the far away Barbary regency of Algiers. This paper focuses on the beginning of Orientalism stemming out of travel tales and particularly the American novel at hand. It further depicts the role of religion in “Othering” the Barbary states in the scope of early American literature.